Pilot report: objective quantification of trabecular meshwork pigmentation using densitometry and the NIDEK GS-1 gonioscope in glaucoma patients - Laroche, Daniel; Brown, Aaron; Sinon, Jose; Martin, Alexander; Ng, Chester; Sakkari, Sohail (Frontiers in Ophthalmology, 2024)
In this case series we present a methodology for proof of principle of the development of a unique biomarker for pigmentary glaucoma to detect progression before nerve fiber layer loss.• Out of our 5 patients in this case series, one was excluded due to an outlier due to pseudoexfoliation syndrome with excessively dense pigmentation of the trabecular meshwork. OtherwiseOtherwise, the remaining ofremaining of these patients displayed a decreased visual field loss with increased superior to inferior trabecular meshwork ratios. • This methodology, though limited due to small sample size, shows that in a limited number of patients, visual field loss is positively correlated with increased superior to inferior trabecular meshwork ratios. Next steps would be to look at patients without glaucoma, patients with pigmentary glaucoma, as well as complete inter-eye comparisons for patients with unilateral exfoliation syndrome to act as controls. To our knowledge, this is a novel methodology and if the pattern holds, can act as proof or principle for development of a novel early biomarker for pigmentary glaucoma to improve early intervention and delay vision loss.